ANALISIS HARGA, TEMPAT TERHADAP KEPUASAN TARUNA-TARUNI AKADEMI MARITIM YOGYAKARTA - Vivid Dekanawati (Majalah Ilmiah Bahari Jogja, 2016)
This study aims to examine "the extent to which price, and place a variable effect on the Cadets satisfaction. The subject of this study are 71 cadets level III of 3 (three) majors available at AMY namely KPN, Nautical and Teknika. The tools used in this study to test the instrument by using SPSS 17.0, F-test, t test and Stepwise test. This research resulted in the discovery of the F test in accordance with the F-count > F-table with a significant level of 0.000 <0.05 (p <0.05), means variables affect the price and place simultaneously against complacency cadets. T-count the price variable is smaller than t-table 1.986 < 2.651 with a probability of (0.051) is greater than the significance level of 0.05, its mean that the price variable has no significant effect on the satisfaction of cadets. For t- test at variable places, t-count is greater than t table (5.361> 2.651) with probability (0.000) is smaller than the significance level of 0.05, its mean that the variable sites had a significant impact on satisfaction cadets. The results of the method stepwise showed that the dominant variable influencing satisfaction of cadets (Y) is a (X2). It is seen from the test stepwise most dominant influence satisfaction cadets (Y) is a (X2). It is also seen from the value of t 5.361 with a probability level of 0,000.